Biogenesis and regulatory hierarchy of phased small interfering RNAs in plants. Issue 5 (23rd February 2018) - Deng, Pingchuan; Muhammad, Sajid; Cao, Min; Wu, Liang
Summary: Several varieties of small RNAs including microRNAs (miRNAs) and small interfering RNAs (siRNAs) are generated in plants to regulate development, genome stability and response to adverse environments. Phased siRNA (phasiRNA) is a type of secondary siRNA that is processed from a miRNA‐mediated cleavage of RNA transcripts, increasing silencing efficiency or simultaneously suppressing multiple target genes. Trans ‐acting siRNAs (ta‐siRNAs) are a particular class of phasiRNA produced from noncoding transcripts that silence targets in trans . It was originally thought that 'one‐hit' and 'two‐hit' models were essential for processing distinct TAS precursors; however, a single hit event was recently shown to be sufficient at triggering all types of ta‐siRNAs. This review discusses the findings about biogenesis, targeting modes and regulatory networks of plant ta‐siRNAs. We also summarize recent advances in the generation of other phasiRNAs and their possible biological benefits to plants.